Penerapan Time and Motion Study pada Proses Produksi di PT. Adis Dimension Footwear - Eka Rifianti; Anti Wulan Agustini (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This community service activity aims to analyze the effectiveness of Time and Motion Study in the production process at PT. Adis Dimension Footwear and provide recommendations for improving work methods. This study employed a qualitative descriptive approach using observation, interviews, and documentation. The results show that implementing Time and Motion Study can enhance work time efficiency, optimize operator movements, and increase productivity by up to 15%. Reducing unnecessary movements, optimizing workflow, and training operators significantly improve production performance. The success of this method depends heavily on socialization, training, and management support. These findings confirm that Time and Motion Study serves not only as a tool for measuring time and movements but also as a strategic instrument for improving efficiency, reducing waste, and increasing overall productivity.